Plant volatiles-loaded core-shell micro-nano fibers to achieve efficient and sustained bisexual attraction to pests - Chenglong Cui; Wenjie Shangguan; Kebin Li; Xingfu Jiang; Zhimin Wang; Jiao Yin; Lidong Cao (Journal of Nanobiotechnology)
Abstract Background Chemical pesticides face significant challenges regarding their efficacy and environmental impact. Plant-based food attractants have emerged as a promising green alternative for pest control. However, their field application is limited by the short duration of effectiveness, necessitating improved carrier systems for sustained release. Electrospinning is a promising technology in this field, with core-shell fibers offering superior performance in efficient loading and sustained release compared to uniaxial fibers, highlighting their potential for further development. Results In this study, core-shell micro-nano fiber mats were prepared via coaxial electrospinning using multiple environmentally friendly polymers. These mats were firstly and successfully loaded with food attractants bisexually attractive to Loxostege sticticalis adults, including 1-octen-3-ol, trans-2-hexenal, linalool, and anethole, enabling sustained release and effective trapping. The components in the core-shell spinning solution were chemically compatible, and after spinning, the poly(3-hydroxybutyrate-co-4-hydroxybutyrate)/polycaprolactone (PHB/PCL) in the shell layer and polyethylene oxide (PEO) in the core layer formed core-shell fibers with clear boundaries. The mats achieved an average encapsulation efficiency of 78% for active ingredients, with a sustained release profile that delivered over 60% of the attractants within 80 days while mitigating early burst release. Electroantennogram and behavioral studies revealed that the mats retained electrophysiological activity for at least 90 days, effectively attracting male and female adult insects even after 75 days. Field trials demonstrated that the mats significantly outperformed commercial slow-release carriers, attracting a higher number of L. sticticalis adults. Additionally, the mats exhibited strong stress resistance, biodegradability, and environmental compatibility, effectively protecting active molecules while minimizing ecological impact. Conclusions The developed fiber mats provide a highly efficient, eco-friendly carrier for plant-based food attractants, offering prolonged efficacy and improved insect trapping performance. This study highlights their potential for sustainable agriculture and pest management, paving the way for greener alternatives to chemical pesticides. Graphical abstract